Association Between the European Society of Cardiology/European Society of Hypertension Heart Rate Thresholds for Cardiovascular Risk and Neuroadrenergic Markers - Guıdo Grassı; Fosca Quarti‐Trevano; Gino Seravalle; Raffaella Dell’Oro; Rita Facchetti; Giuseppe Mancia (2020)
The recent European Society of Cardiology/European Society of Hypertension hypertension guidelines identify resting heart rate (HR) values >80 bpm as predictors of cardiovascular risk, with the unproven assumption that this might reflect the presence of a sympathetic overdrive. In the present study, we tested this hypothesis throughout the use of direct and indirect sympathetic markers. In 193 untreated moderate essential hypertensives aged 50.4±0.6 years (mean±SEM), we measured clinic and ambulatory blood pressure and corresponding HR, venous plasma norepinephrine (high performance liquid chromatography), and muscle sympathetic nerve traffic (microneurography). We then subdivided the study population into 2 groups according to HR < or >80 bpm. Eighty-four patients displayed resting HR >80 bpm, which was this cutoff value in the remaining 109 patients, the 2 groups showing superimposable age, and sex distribution. Clinic and ambulatory blood pressure were similar in the 2 groups, whereas left ventricular mass index was significantly greater in the group with HR >80 bpm. Muscle sympathetic nerve traffic values were also significantly greater in this latter group (72.77±0.9 versus vs 36.83±1.3 bursts/min, P <0.0001); this being the case also for norepinephrine (293.0±8.7 versus 254.1±8.9 pg/mL, P <0.002). In the whole population, there was a significant direct relationship between muscle sympathetic nerve traffic, norepinephrine, left ventricular mass index, and HR values. Similar results were obtained when 24-hour HR values were analyzed. Thus patients with hypertension displaying HR >80 bpm are characterized by a marked sympathetic overdrive, particularly when direct adrenergic markers are used. This finding suggests that cardiac and peripheral sympathetic activation are involved in the increased cardiovascular risk detected in this group of patients.